2006
DOI: 10.1111/j.1365-2934.2006.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of reflexology foot massage to reduce anxiety in hospitalized cancer patients in chemotherapy treatment: methodology and outcomes

Abstract: Reflexology foot massage can be considered a support treatment used in combination with traditional medical treatments and executed by an expert, qualified person to help cancer patients receiving chemotherapy feel better and also cope better with their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 26 publications
3
57
0
4
Order By: Relevance
“…This finding is in harmony with Quattrin et al 2000) studies which revealed that reflexology massage improve physical activities (46,47,48,49,50) . Siev-Ner et al (2003) stated that when reflexology massage was applied 3 times for 2 weeks, it was noticed that by the end of the first week, that there was significant improvement in doing anything during the day, doing things around the house and rearranged the entire house (42) .…”
Section: Effect Of Reflexology Foot Massage On Leg Cramps For Patientsupporting
confidence: 77%
“…This finding is in harmony with Quattrin et al 2000) studies which revealed that reflexology massage improve physical activities (46,47,48,49,50) . Siev-Ner et al (2003) stated that when reflexology massage was applied 3 times for 2 weeks, it was noticed that by the end of the first week, that there was significant improvement in doing anything during the day, doing things around the house and rearranged the entire house (42) .…”
Section: Effect Of Reflexology Foot Massage On Leg Cramps For Patientsupporting
confidence: 77%
“…Quattrin et al's (2006) study showed a significant decrease in systolic blood pressure (p <0.001) and a significant decrease in diastolic blood pressure (p <0.05) in cancer patients with chemotherapy after foot massage. In addition, Chacko's (2007) also found a significant reduction in blood pressure in post-surgical abdominal patients after foot massage (p <0.05).…”
Section: Discussionmentioning
confidence: 84%
“…Foot massage has also been found to have an effect on the reduction of lower limb edema in pregnancy (Coban & Sirin, 2010), decreased anxiety and depression in palliative care (Puthusseril, 2006), decreased agitation in dementia patients (Moyle, Johnston, & O'Dwyer, 2011 ), as well as decreased pain, depression, anxiety, stress, and weakness in cancer patients (Cassileth & Vickers, 2004;Quattrin et al, 2006;Falkensteiner et al, 2011;Kim & Oh, 2011). This study finding in line with Hayes and Cox'x's study found that a significant reduction of Mean Arterial Pressure (MAP) of 25 patients at Intensive Care Unit (ICU) after foot massage (Smith et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of these studies suggest that reflexology in patients with breast and lung cancer causes diminished pain and anxiety and decreased pain in metastatic cancer patients [16,17]. It has also led to lowered anxiety [18] in patients suffering from non-metastatic cancers undergoing chemotherapy. In the available studies, further research has been recommended to be conducted on this group of patients with a larger sample volume [16].…”
Section: Introductionmentioning
confidence: 80%